PENERAPAN PENDEKATAN DEEP LEARNING TERHADAP PEMBELAJARAN MATEMATIKA KELAS RENDAH DI MI SENTRA CENDEKIA MUSLIM - Nur Fatimah; Zul Andrivat (MURABBI, 2025)
This study aims to analyze the application of the Deep Learning approach in mathematics learning in the lower class at MI Muslim Scholars Center. The Deep Learning approach is used to foster students' conceptual understanding, critical thinking, and reflective abilities towards basic math material. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of teachers and students in grade I of the Muslim Scholars Center. The results of the study show that the application of the Deep Learning approach can increase student learning activity and motivation through student-centered learning activities, such as group discussions, exploration of contextual problems, and reflection on learning outcomes. Students show improved ability to understand number concepts, basic calculation operations, and the application of concepts in daily life. In addition, teachers play an important role as facilitators in directing the deep thinking process and ensuring the active involvement of each student. Thus, the application of the Deep Learning approach has proven to be effective in improving the quality of mathematics learning in low grades, and can be used as an innovative alternative in an effort to improve numeracy competence in madrasah-based elementary schools.